2010
DOI: 10.1128/aac.01450-09
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Experience with the Use of Doripenem against Extended-Spectrum-β-Lactamase-Producing and Ciprofloxacin-Resistant Enterobacteriaceae : Analysis of Six Phase 3 Clinical Studies

Abstract: The worldwide increase in fluoroquinolone-resistant and extended-spectrum ␤-lactamase (ESBL)-producing Enterobacteriaceae pathogens has led to doripenem and other carbapenems assuming a greater role in the treatment of serious infections. We analyzed data from 6 phase 3 multinational doripenem clinical trials on ciprofloxacin-resistant Enterobacteriaceae isolates consisting of all genera (CIPRE) and ESBL-producing Enterobacteriaceae isolates consisting of Escherichia coli, Klebsiella spp., and Proteus spp. wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 14 publications
1
18
0
1
Order By: Relevance
“…64,91 The available data are limited for doripenem; a recently study performed a post hoc analysis of 6 randomised clinical trials evaluating doripenem in infections caused by ESBLproducers (1 in complicated UTI [cUTI] in comparison with levofloxacin, 2 in complicated intraabdominal infections [cIAI] in comparison with meropenem and 2 in hospital-acquired pneumonia [HAP], one compared to piperacillin/tazobactam and the other in comparison with imipenem); overall, 20/30 (61.7%) of patients treated with doripenem had a favourable outcome at test of cure, similar to comparators (24/39, 61.5%). 96 The numbers were too low to make comparisons with specific drugs or for specific indications.…”
Section: Which Carbapenem Should Be Used For Esbl-producers?mentioning
confidence: 99%
“…64,91 The available data are limited for doripenem; a recently study performed a post hoc analysis of 6 randomised clinical trials evaluating doripenem in infections caused by ESBLproducers (1 in complicated UTI [cUTI] in comparison with levofloxacin, 2 in complicated intraabdominal infections [cIAI] in comparison with meropenem and 2 in hospital-acquired pneumonia [HAP], one compared to piperacillin/tazobactam and the other in comparison with imipenem); overall, 20/30 (61.7%) of patients treated with doripenem had a favourable outcome at test of cure, similar to comparators (24/39, 61.5%). 96 The numbers were too low to make comparisons with specific drugs or for specific indications.…”
Section: Which Carbapenem Should Be Used For Esbl-producers?mentioning
confidence: 99%
“…Analysis of 1,772 clinical www.intechopen.com E. coli isolates (many from complicated UTIs) found that 99.8% of them were susceptible to doripenem, including all 30 ESBL-producers (Pillar et al, 2008). Analysis of 6 Phase III clinical trials demonstrated that doripenem was as effective as levofloxacin, imipenem, meropenem and piperacillin-tazobactam in treatment of patients with complicated UTIs due to ciprofloxacin-resistant and ESBL-producing Enterobacteriaceae (largely UPEC) (Kaniga et al, 2010). Prulifloxacin is a fluoroquinolone approved for treatment of UTIs in Italy and Japan, but not yet approved in the US.…”
Section: Newer Uti Therapies 331 Recently Approved Therapiesmentioning
confidence: 99%
“…Дорипенем, вошедший в клиническую практику в 2007 г., дополнил группу антисинегнойных карбапенемов: имипе-нем/циластатин (1985) и меропенем (1996). Дорипенем по микробиологическим показателям на момент регистрации отличался от других карбапенемов более высокой актив-ностью в отношении псевдомонад [2]. Сначала дорипенем был зарегистрирован в США, затем в Европе, России и ряде стран Азии по следующим показаниям: осложненные абдоминальные инфекции, осложненные уроинфекции и пиелонефрит, нозокомиальная пневмония, в том числе связанная с искусственной вентиляцией легких (НПивл), так как к этому времени были получены результаты реги-страционных исследований по этим показаниям.…”
unclassified